Lenvatinib plus transarterial chemoembolization with or without immune checkpoint inhibitors for unresectable hepatocellular carcinoma: A review - Sun, Liwei; Xu, Xuelong; Meng, Fanguang; Liu, Qian; Wang, Hankang; Li, Xiaodong; Li, Guijie; Chen, Feng (Frontiers in Oncology, 2022)
Lenvatinib plus transarterial chemoembolization (TACE)have become the first choice for patients with hepatocellular carcinoma (HCC) that are unsuitable for TACE. Sorafenib plus TACE therapy for patients with portal vein tumor thrombus (PVTT) achieved positive results. However, Lenvatinib plus TACE appeared to achieve a more advantageous result for these patients based on the phase 3 REFLECT trial. Both TACE and lenvatinib therapy have immune-stimulating effects, so would lenvatinib plus TACE and immune checkpoint inhibitors be an advantageous therapy for unresectable HCC (uHCC)? Thirteen articles from PubMed were explored to determine the efficacy and safety of lenvatinib plus TACE with or without PD-1 inhibitors therapy. Most of the adverse events (AEs) were manageable. Lenvatinib plus TACE therapy was superior to lenvatinib monotherapy with intermediate stage HCC especially beyond up-to-seven criterion and was superior to TACE monotherapy in patients with uHCC or sorafenib plus TACE therapy in patients with PVTT. Objective response rates (ORRs) of 53.1%–75%, median progression free survival (PFS) of 6.15–11.6 months, and median overall survival (OS) of 14.5–18.97 months were achieved in the lenvatinib plus TACE group. Levatinib plus TACE and PD-1 inhibitors achieved ORRs of 46.7% –80.6%, median PFS of 7.3–13.3 months, and median OS of 16.9–24 months. Control studies also confirmed the triple therapy was superior to lenvatinib plus TACE in patients with uHCC. Overall, the triple therapy is a promising treatment for patients with uHCC, including main PVTT and extrahepatic metastasis. Lenvatinib plus TACE therapy was also preferable for intermediate stage HCC beyond up-to-seven criterion and for patients with PVTT.